Environmentally induced ribosomal DNA (rDNA) instability in human cells and populations exposed to hexavalent chromium [Cr (VI)]. (August 2021) - Lou, Jianlin; Yu, Shoukai; Feng, Lingfang; Guo, Xinnian; Wang, Meng; Branco, Alan T.; Li, Tao; Lemos, Bernardo
Highlights: The nucleolus, an intranuclear organelle, has been implicated in aging and cancer. The ribosomal DNA (rDNA) array displays variable copy number and gives origin to nucleolus. Exposure to hexavalent chromium [Cr (VI)] triggers cycles of rapid but transient amplification of the rDNA. Genetic variation in the rDNA is exquisitely dynamic and environmentally responsive. Our observations identify a novel pathway of response to Cr (VI) exposure. Abstract: Hexavalent Chromium [Cr (VI)] is an established toxicant, carcinogen, and a significant source of public health concern. The multicopy ribosomal DNA (rDNA) array is mechanistically linked to aging and cancer, is the most evolutionarily conserved segment of the human genome, and gives origin to nucleolus, a nuclear organelle where ribosomes are assembled. Here we show that exposure to Cr (VI) induces instability in the rDNA, triggering cycles of rapid, specific, and transient amplification and contraction of the array in human cells. The dynamic of environmentally responsive rDNA copy number (CN) amplification and contraction occurs at doses to which millions of individuals are regularly exposed. Finally, analyses of human populations occupationally exposed to Cr (VI) indicate that environmental exposure history and drinking habits but not age shape extensive naturally occurring rDNA copy number variation. Our observations identify a novel pathway of response to hexavalent chromium exposure and raise the prospect that a suite of environmental determinants of rDNA copy number remain to be discovered.